Peningkatan Kesadaran dan Kepatuhan Pajak melalui Program Relawan Pajak: Pendampingan Pelaporan SPT dan Edukasi Digital - Trisna Gayatri; Danang Adi Putra; Amir Mahmud; Delisa Lestari (Jaanur Elbarik Indonesia, 2026)
This community service activity aims to improve public tax literacy and compliance through assistance in reporting Annual Tax Returns and digital tax education. The implementation method includes recruitment and training of students as volunteers, outreach through seminars and digital media, direct assistance in reporting Tax Returns, and education based on interactive modules and digital content. Evaluation was carried out through pre- and post-tests, satisfaction surveys, and analysis of the number of Tax Returns successfully filed. The results of the activity showed a significant increase in tax understanding, formal compliance, and utilization of e-filing services, with more than 85% of participants able to report Tax Returns independently. This program also strengthens the role of students as agents of change and has the potential to become a national model for strengthening a digital-based tax awareness culture